Spatial Distribution in Tree Species Composition, Abundance and Diversity in Embobut River Basin - Wanjohi, B. K.; Njenga, E. W.; Sudoi, V.; Kipkore, W. K.; Moore, H. L.; Davies, M. I. J. (Africa Environmental Review Journal, 2022)
Embobut Forest Reserve in Elgeyo Marakwet County is one of the five major water towers in Kenya where there is increasing encroachment by humans for settlement and agriculture. Therefore, the influence of settlement activities and biodiversity changes need to be assessed. This study carried out an inventory to monitor the distribution of trees in terms of species composition, abundance and diversity in Embobut River Basin along an altitudinal gradient characterized by valley floor, escarpment, upper forested area and the moorland/montane region. Transect and quadrant methods were used as sampling techniques. A checklist was used to characterize tree species composition with a corresponding presence/absence data at each of the site blocks. Species distribution in terms of presence/absence and abundance was determined using cluster analysis. The results showed that there were 41 tree species belonging to 24 families. The valley floor had the highest frequency of tree (16) followed by escarpment (15), then upland forests (9) and least in montane region (8). No single species occurred at all site probably due to high degree of specialization in their endemic ecological zone. Few species such as Vachelia tortilis, Senegalia meliffera, Boscia coriacea, Bersama abysinica and Balanites pedicellaris showed wide distribution in terms of composition and abundance beyond their native habitats. The montane region had the highest species diversity followed by escarpment and the least abundant region was the valley floor. The present study demonstrates low distribution in tree composition, abundance and diversity which may have resulted from human encroachment of the Embobut River Basin.